2013
DOI: 10.3126/banko.v22i2.9198
|View full text |Cite
|
Sign up to set email alerts
|

Landslide hazard zonation, mapping and investigation of triggering factors in Phewa lake watershed, Nepal

Abstract: The landslide triggering factors were investigated followed by the thematic maps and landslide distribution map prepared and classified using the GPS and GIS Softwares like CartaLinx, ArcView and ERDAS IMAGINE in Sarangkot and Kaskikot Village Development Committees, Kaski district. In analytical hierarchy process, the factors for zonation were compared by Couple Comparison Method and their weights were determined using Arithmetic Mean Method and earned weight values of each factor. The landslide hazard zonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Thulibesi phant in Armala, where 117 sinkhole spots were observed, is exposed to severe sinkhole hazards [55]. Sarangakot and Kaskikot within the Phewa watershed [56] and the Rupakot area of the Rupa watershed [57] are prone to landslide hazards. The Phewa Lake catchment area in Pokhara witnessed a shallow seated landslide due to extreme rainfall in 2007 [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thulibesi phant in Armala, where 117 sinkhole spots were observed, is exposed to severe sinkhole hazards [55]. Sarangakot and Kaskikot within the Phewa watershed [56] and the Rupakot area of the Rupa watershed [57] are prone to landslide hazards. The Phewa Lake catchment area in Pokhara witnessed a shallow seated landslide due to extreme rainfall in 2007 [51].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed geographical study of Pokhara, Kaski was carried out by Gurung in 1965 [66]. Yet, there are few studies have assessed the hazard risk scenario [54][55][56][57][58] and urbanization trends [67,68] of Pokhara City and the Seti watershed [8]. However, long-term time-series studies of urbanization and the hazard risk of the entire Kaski District is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…With 556 landslides, the landslide density in the Panchase area was found to be 1.99 per km 2 . In research conducted at a location nearby this experimental site, landslide densities of 0.44 per km 2 (Basnet et al, 2006) and 0.571 per km 2 (Bhatt et al, 2013) were found in Phewa and Rupa watersheds, respectively. Phewa watershed is a part of the present study area.…”
Section: Landslide Inventorymentioning
confidence: 92%
“…In the case of land use, we can observe a higher amount of landslide area in forests and cultivated lands which are 0.762 km 2 and 0.358 km 2 respectively which together accounted for 75% of the total landslide area. A study in Phewa watershed had also found higher landslides among forests (Basnet et al, 2006) whereas cultivation lands had higher landslides in a study at Mugu District (Budha et al, 2016). Bhatt et al (2013) also found higher landslides in cultivated lands than in forests.…”
Section: Factors Influencing Landslide Hazardmentioning
confidence: 92%
See 1 more Smart Citation